Phosphorylation at Serines 157 and 161 Is Necessary for Preserving Cardiac Expression Level and Functions of Sarcomeric Z-Disc Protein Telethonin - Lewis, Hannah R.; Eminaga, Seda; Gautel, Mathias; Avkiran, Metin (Frontiers in Physiology, 2021)
Aims: In cardiac myocytes, the sarcomeric Z-disc protein telethonin is constitutively bis phosphorylated at C-terminal residues S157 and S161; however, the functional significance of this phosphorylation is not known. We sought to assess the significance of telethonin phosphorylation in vivo, using a novel knock-in mouse model generated to express non phosphorylatable telethonin (TcapS157/161A). Methods and Results: TcapS157/161A and wild-type littermates were characterized by echocardiography at baseline and after sustained β-adrenergic stimulation via isoprenaline infusion. Heart tissues were collected for gravimetric, biochemical and histological analyses. At baseline, TcapS157/161A mice did not show any variances in cardiac structure or function compared with wild-type littermates and mutant telethonin remained localized to the Z disc. Ablation of telethonin phosphorylation sites resulted in a gene dosage dependent decrease in the cardiac telethonin protein expression level in mice carrying the S157/161A alleles, without any alteration in telethonin mRNA levels. The proteasome inhibitor MG132 significantly increased the expression level of S157/161A telethonin protein in myocytes from TcapS157/161A mice, but not telethonin protein in myocytes from wild-type mice, indicating a role for the ubiquitin-proteasome system in the regulation of telethonin protein expression level. TcapS157/161A mice challenged with sustained β adrenergic stimulation via isoprenaline infusion developed cardiac hypertrophy accompanied by mild systolic dysfunction. Furthermore, the telethonin protein expression level was significantly increased in wild-type mice following isoprenaline stimulation but this response was blunted in TcapS157/161A mice. Conclusions: Overall, these data reveal that telethonin protein turnover in vivo is regulated in a novel phosphorylation-dependent manner and suggest that C-terminal phosphorylation may protect telethonin against proteasomal degradation and preserve cardiac function during hemodynamic stress. Given that human telethonin C-terminal mutations have been associated with cardiac and skeletal myopathies, further research on their potential impact on phosphorylation-dependent regulation of telethonin protein expression could provide valuable mechanistic insight into those myopathies.